IMPLEMENTASI KEBIJAKAN PENGANGKATAN TENAGA HONORER MENJADI APARATUR SIPIL NEGARA DI KABUPATEN JAYAPURA - Agustina Pepuho; Untung Muhdiarta (Universitas Cenderawasih, 2021)
The purpose of the study was to determine the implementation of the policy on the appointment of honorary workers to become ASN, the supporting and inhibiting factors in the appointment of honorary workers to become ASN in Jayapura Regency based on the efforts made in solving the problem of appointing honorary workers to ASN in Jayapura Regency. The research method used in this research is descriptive qualitative by describing the implementation of the policy on the appointment of honorary staff to become ASN in Jayapura Regency based on Government based on the theory of Edward III. Informants in this study consisted of; 1 Head of District 1 BKPSDM Office, Head of Sub-dept. of Mutations and 1 Head of Sub-Procurement and 3 honorary staff. The analysis of this research, namely data collection, data reduction, data presentation and conclusion drawing. The results of the analysis obtained that the implementation of the communication and coordination indicators has not been maximized, because in the appointment of honorary staff there is no clarity between honorary staff and first aid workers. The availability of human resources has been very good for the appointment of Honorary Personnel charged to the regional revenue and expenditure budget. The facility is authorized by the Regional Personnel Agency of Jayapura Regency. The bureaucratic structure is good. The supporting factor is the existence of government regulation policy No. 56 of 2012 in favor of K1 honorary staff, information that is easily and quickly accessed by all honorary staff in delivering information through radiograms of each agency, bulletin boards and online information. As well as a quick re-verification update by BKPSDM through an independent team in the public test and informed through the Jayapura district government portal, so that non-verified honorary staff can re-verify, because the public test was carried out 3 times. The inhibiting factor is the lack of good communication between BKPSDM and other regional apparatus related to the requirements to become honorary staff and PPPK because of the lack of socialization regarding the administrative completeness of the selection of ASN candidates, so that during verification there were honorary staff who did not pass the verification. This is certainly detrimental to honorary staff who have served for several years, especially for honorary workers classified as K2. In addition, there are indications of data errors that indicate collusion and nepotism.